Pengembangan Sistem Informasi Lembaga Bimbingan Belajar Al-Hasyimi - Muhammad Jauhar Fuadi; Retno Indah Rokhmawati; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Lembaga Bimbingan Belajar (LBB) Al-Hasyimi is a private educational institution that providing study guidance in reading the Holy Koran and Iqro' both by private and by group. In managing student's study result, LBB Al-Hasyimi still uses a conventional method. Every mentor has to note their student's study result in the book which called by â€œBuku Prestasi Siswaâ€. Then this book would be recapped by secretary once in every month. In the other hand, the mentor had to do checking presence after guiding too. By using information technology, the problem can be simplified by using Lembaga Bimbingan Belajar Al-Hasyimi Information System based on website which developed by using waterfall method. This development method covered requirement analysis, design, implementation and testing. On the requirement analysis produced business process to-be that created based on the result of stakeholder interview and problem analysis. The result of the requirement analysis visualized in use case diagram. The result of the system design produced sequence diagram, class diagram, physical data model, pseudocode algorithm, user interface, and testing design. On its implementation, this system developed by using CodeIgniter framework by applying the Model-View-Controller pattern. The result of Validation Testing on 6 test case got as many as 100% valid. Then the result of User Acceptance Testing (UAT) on some features, there are adding a study result, seeing a study result, seeing a tentor absence, and complaining got average percentage more than 80%. With the result of UAT revealed that Lembaga Bimbingan Belajar Al-Hasyimi Information System already accepted by user.